ANALISIS INDEKS KEANDALAN STASIUN LAYANG MASS RAPID TRANSIT JAKARTA BERDASARKAN KEGAGALAN RATA-RATA PERALATAN SISTEM DISTRIBUSI - Zainal Arifin; John Pantouw; Sahrul Anwar (Sutet, 2018)
Mass Rapid Transit (MRT) is an effective mass- transportation mode that has been proven by many in major cities in different countries. This will be applied in Indonesia but still limited to Jakarta which will be managed by PT. Mass Rapid Transit Jakarta (MRTJ). The MRTJ is targeted to carry 173,000 people a day. The purpose of this MRTJ development is to reduce the use of private transportation and switch to public transportation so as to reduce traffic congestion. Electricity as a source of this transportation means must be guaranteed reliability. Proper configuration, reliable equipment and automated system operation will provide a good distribution system performance. With the smooth progress of electric power to consumers, the more reliable a distribution system. With the prediction of 99.5% to 99.9999% availability of electricity supply is expected to ensure the reliability of the MRTJ power supply system.